Forgiveness, future orientation, and adolescent aggression: a correlational study - Mikaela Berliyana Alitani; Yeny Duriana Wijaya; Kamalia Kamalia (Jurnal Konseling dan Pendidikan, 2026)
Aggressive behavior among adolescents remains a concern in high-density and socially vulnerable areas such as Johar Baru District, Central Jakarta. Existing studies have rarely examined the relative roles of emotional and cognitive factors within such contexts. This study addresses this gap by examining the association between forgiveness, future orientation, and adolescent aggressiveness using a quantitative, non-experimental correlational design. A total of 100 adolescents aged 10–17 years were selected through purposive sampling. Data were collected using validated scales and analyzed with Spearman’s rank correlation due to non-normal data distribution. The results showed a moderate, significant negative association between forgiveness and aggressiveness (ρ = −0.419; p < 0.05), while future orientation was weak and not significant (ρ = −0.181; p > 0.05). These findings indicate that forgiveness is associated with lower aggressiveness, although the effect size suggests a partial contribution alongside contextual factors. Given the correlational design, causal claims cannot be made. Limitations include non-random sampling and self-report bias. The study highlights the importance of emotional processes while emphasizing the need to consider broader social conditions.